2020
DOI: 10.29271/jcpsp.2020.08.796
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immature Platelet Fraction (IPF) in Patients with Central Thrombocytopenia and Peripheral Thrombocytopenia

Abstract: Objective: To determine immature platelet fraction (IPF) in patients with thrombocytopenia and correlation with their bone marrow findings and to determine its predictive value in differentiating peripheral (hyper destructive) thrombocytopenia from central (hypo-productive) thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Ashraf et al in their study found that patients with central thrombocytopenia had a median IPF of 8.2 (IQR=4.6-16.7), which was substantially lower than patients with peripheral thrombocytopenia, who had a median IPF of 25.5 (IQR=15.2-39.3) with a p-value of 0.001. IPF can thus be used to distinguish between central and peripheral thrombocytopenia, according to this study [ 7 ]. Additionally, Li et al discovered that the IPF% was significantly lower in the group with reduced platelet production compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashraf et al in their study found that patients with central thrombocytopenia had a median IPF of 8.2 (IQR=4.6-16.7), which was substantially lower than patients with peripheral thrombocytopenia, who had a median IPF of 25.5 (IQR=15.2-39.3) with a p-value of 0.001. IPF can thus be used to distinguish between central and peripheral thrombocytopenia, according to this study [ 7 ]. Additionally, Li et al discovered that the IPF% was significantly lower in the group with reduced platelet production compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…These platelets reflect the bone marrow's ability to generate platelets and may be used as a surrogate marker for megakaryocytic activity [ 5 ]. According to studies, IPF is raised in patients with peripheral platelet destruction and decreased or normal in people who have central thrombocytopenia [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%